LRRK2 mediates α-synuclein-induced neuroinflammation and ferroptosis through the p62-Keap1-Nrf2 pathway in Parkinson’s disease - Liu, Xinjie; Zheng, Zijian; Xue, Cheng; Wang, Xiangrong; Li, Jianwei; Liu, Zheng; Xin, Wenqiang; Xu, Xinping; Zhou, Dongwei; Yao, Longping; Lu, Guohui (Inflammation, 2025)
Parkinson’s disease (PD) is the second most prevalent neurodegenerative disorder worldwide, characterized by the progressive degeneration of dopaminergic neurons in the substantia nigra pars compacta and the abnormal aggregation of α-synuclein (α-syn). Despite extensive research, the mechanisms underlying microglial-mediated neuroinflammation and ferroptosis in PD remain inadequately understood. In particular, the role of leucine-rich repeat kinase 2 (LRRK2) in microglial cells and its modulation of the p62-Keap1-Nrf2 signaling pathway warrant further investigation.In this study, we present novel findings demonstrating that LRRK2 regulates microglial neuroinflammation and ferroptosis through the p62-Keap1-Nrf2 signaling axis in the context of PD. Using α-syn-stimulated BV2 microglial cells, we found that LRRK2 inhibition significantly reduced the production of pro-inflammatory cytokines and enhanced the activation of the p62-Keap1-Nrf2 pathway, thereby mitigating ferroptosis and oxidative stress. Furthermore, conditioned medium from LRRK2-inhibited microglia conferred neuroprotective effects on cultured neurons, highlighting the therapeutic potential of targeting LRRK2 in microglia.Importantly, these in vitro findings were corroborated in the MPTP-induced PD mouse model, where LRRK2 inhibition led to diminished microglial activation, decreased apoptosis of midbrain dopaminergic neurons, and upregulation of the p62-Keap1-Nrf2 pathway.Our study fills a critical gap in understanding the microglial mechanisms mediated by LRRK2 and provides novel insights into the pathogenesis of PD. These findings suggest that targeting LRRK2 in microglia may represent a promising therapeutic strategy for PD.